Pengaruh Kualitas Pelayanan, Sarana Prasarana terhadap Kepuasan dan Loyalitas Siswa di SMPIT Muhammadiyah Pangkalan Kerinci - Rizkiyani, Elvi Sri; Gusnardi; Gimin (Universitas Pendidikan Ganesha, 2025)
Student loyalty refers to a strong commitment upheld by students to continuously support the services they receive, even to the extent of influencing prospective students to also experience those services. Several factors can influence student loyalty, namely customer satisfaction, service quality, and the facilities and infrastructure provided by the school itself. Therefore, it is important for individuals to develop a high level of loyalty to the school they have chosen. Through such loyalty, individuals can help maintain the school’s reputation and contribute to better achievements, both on an individual and collective level.This study aims to analyse the influence of service quality and facilities on loyalty, mediated by satisfaction. The sampling method used was saturated sampling, whereby the entire population was taken as the sample, comprising 34 students. Data were collected through a questionnaire, and the data analysis was conducted using SEM-PLS (Structural Equation Modelling - Partial Least Squares).The findings indicate that service quality and facilities can influence loyalty through satisfaction. Therefore, improving service quality and providing adequate facilities and infrastructure are key factors in building student satisfaction, which in turn has a positive impact on loyalty.